Physiological and behavioral responses of juvinile mud crab (scylla serrata) to mercury. - Monteclaro, Harold M. (University of the Philippines, 2007)
Mortality of juvenile mud crab Scylla serrate was evaluated using a renewal-type acute toxicity study. Three hundred sixty individuals were subjected to six mercury, concentrations for a period of 96 h. The 96 h LC50 was computed at 0.04113 ppm. Juvenile crabs that survived the acute toxicity test were transferred to clean waters, fed daily and monitored for 3 weeks. Juvenile crabs previously exposed in 0.0550 ppm Hg for 96 h had low survival rates. This result suggests that escape from exposure of high mercury concentrations does not guarantee survival for the juveniles. Avoidance of juvenile mud crabs to mercury was determined using a fluvarium, which provided the crabs a choice between untreated and Hg-treated waters. Avoidance threshold of native juvenile crabs was estimated at 0.1 ppm, a concentration that is more than twice the 96 h LC50 value. Previous exposure of juvenile crabs in mercury could alter their ability to detect and avoid mercury. Juveniles previously pre-exposed in 1/50th of the 96-h LC50 value. Previous exposure of juvenile crabs in mercury could alter their ability to detect and avoid mercury. Juveniles previously pre-exposed in 1/50th of the 96-h LC50 value had a higher avoidance threshold at 1 ppm, making them more susceptible to mortality, bioaccumulation, and possible abnormal development. Juvenile mud crab's inability to avoid waters containing sublethal levels of mercury could affect crab biomass, distribution, growth, development, and chemoreception, which consequently affect capture fisheries, aquaculture and safety of fishery products.